Household Contacts as Risk Factor for Tuberculosis: A Cross-Sectional Study - Oktaviana, Ardyawati Wira; Sofiana, Liena; Muthiah, Tisa Salma (Universitas Ahmad Dahlan, 2024)
Background: Tuberculosis (TBC), caused by Mycobacterium tuberculosis, is an infectious disease that is still a global problem. Indonesia has a high burden of pulmonary tuberculosis and is ranked second in the world with the highest number of TBC sufferers after India. Tuberculosis is transmitted through infected droplets when coughing or sneezing, and close contact is very susceptible to the transmission process and other supporting factors. This study aims to determine the risk factors for TBC. Method: This study used a cross-sectional research design with Chi-Square analysis and continued with multivariate analysis and logistic Regression. The sample consisted of 430 respondents obtained using the Accidental Sampling technique. Results: Factors associated with TBC in the Kapanewon Depok area were age (RP: 2.086; 95% CI: 1.247-3.490; p= 0.006), gender (RP: 2.1; 95% CI: 1.302-3.393; p= 0.003), family income (RP: 3.593; 95% CI: 2.322-5.560; p= 0.000), history of household contact (RP: 8.438; 95% CI: 5.737-12.410; p= 0.000), and history of close contact (RP: 3.881; 95% CI: 2.49-6.051; p= 0.000). The factor that has the most influence on the incidence of TBC is a history of household contact with a value of Exp(B)=17.699. Conclusion: Risk factors for pulmonary TBC in the Kapanewon Depok area are age, gender, family income, history of household contact, and history of close contact. A relationship, namely the history of household contact, has the most influence on the incidence of TBC in the Kapanewon Depok area.